The Role of Universities in Sustainable Ecological Development with Reference to Montenegro - Savo Markovic (Journal of Sustainability Perspectives, 2023)
From the moment Montenegro became an ecological state in 1991 and defined its strategic commitment to adopt and apply the highest norms and standards in the field of environmental protection, until today, it can be stated that very little has been done in practice. The role of the scientific community in such a chaotic system should be crucial in terms of supporting and developing study programs oriented towards nature conservation, environmental protection, and the adoption of the concept of strategic development that is ecologically sustainable. Citizens increasingly recognize and feel the consequences of bad decisions by those who do not want to face the avalanche of environmental problems in Montenegro. The role of the university as a higher education scientific research institution should be crucial in managing future education in this area, through full support for sustainable development and providing examples of good practice. This paper will investigate to what extent and in what way Montenegrin universities contribute to sustainable development, including their curricula, programs, contents, and overall activity focused on "green" business.